Hospitalization and Mortality Risk for COVID-19 Cases With SARS-CoV-2 AY.4.2 (VUI-21OCT-01) Compared to Non-AY.4.2 Delta Variant Sublineages . (20th February 2022) - Nyberg, Tommy; Harman, Katie; Zaidi, Asad; Seaman, Shaun R; Andrews, Nick; Nash, Sophie G; Charlett, Andre; Lopez Bernal, Jamie; Myers, Richard; Groves, Natalie; Gallagher, Eileen; Gharbia, Saheer; et al.
Abstract: To investigate if the AY.4.2 sublineage of the SARS-CoV-2 delta variant is associated with hospitalization and mortality risks that differ from non-AY.4.2 delta risks, we performed a retrospective cohort study of sequencing-confirmed COVID-19 cases in England based on linkage of routine health care datasets. Using stratified Cox regression, we estimated adjusted hazard ratios (aHR) of hospital admission (aHR = 0.85; 95% confidence interval [CI], .77–.94), hospital admission or emergency care attendance (aHR = 0.87; 95% CI, .81–.94), and COVID-19 mortality (aHR = 0.85; 95% CI, .71–1.03). The results indicate that the risks of hospitalization and mortality are similar or lower for AY.4.2 compared to cases with other delta sublineages. Abstract : COVID-19 cases with the AY.4.2 sublineage of the delta variant had lower or similar risks of hospital admission, hospital admission or emergency care attendance, and COVID-19 mortality compared to cases with other delta variant sublineages.